Raine syndrome: Prenatal diagnosis based on recognizable fetal facial features and characteristic intracranial calcification. (14th September 2020) - El‐Dessouky, Sara H.; Abdel‐Hamid, Mohamed S.; Abdel‐Ghafar, Sherif F.; Aboulghar, Mona M.; Gaafar, Hassan M.; Fouad, Mona; Ahmed, Adel H.; Abdel‐Salam, Ghada M. H.
Abstract: Objective: The purpose of this study was to elucidate the facial morphology and the pattern of internal malformations in three fetuses with RS born to first cousins of Egyptian decent. Methods: The fetal ultrasonography findings were highly suggestive of RS leading to targeted Sanger sequencing of FAM20C and postnatal assessment. Results: The prenatal ultrasound findings of osteosclerotic skull, exorbitism, hypoplastic nose, midface hypoplasia, small mouth with down‐curved corners, and a distinct and recognizable pattern of intracranial calcification were identified in three fetuses with RS. The calcifications were evident specifically around the corpus callosum and/or ventricular walls. Ectopic renal and hepatic calcifications, pulmonary hypoplasia, mild rhizomelic shortening of the upper limbs, intrauterine fractures, and cerebellar hypoplasia were also noted. Molecular analysis identified three novel homozygous variants, two frameshift: [c.456delC (p.Gly153Alafs*34)] in exon 1 and [c.905delT (Phe302Serfs*35)] in exon 4 and one nonsense mutation in exon 10, [c.1557C>G(p.Tyrs519*)]. The three variants were segregated with the phenotype. This is the first description of a phenotype associated with homozygous truncating variants of FAM20C. Conclusion: RS has characteristic prenatal ultrasound findings which can improve the prenatal identification of this condition and help in guiding the molecular diagnosis and counseling.